1988
DOI: 10.1139/v88-038
|View full text |Cite
|
Sign up to set email alerts
|

Cinétique et mécanisme des réactions bromate–chlorite et bromate – dioxyde de chlore

Abstract: In an acidic solution, containing initially chlorous acid and bromate in excess, two consecutive reactions are observed, the oxidation of chlorous acid to chlorine dioxide followed by the oxidation of chlorine dioxide: BrO3− + 4ClO2 + 2H2O = 4ClO3− + 3H+ + HOBr. The kinetics of this reaction has been studied and a mechanism proposed. It agrees with the one accepted for the related reaction between bromate and Ce(III). Extended by reactions of chlorous acid, the mechanism reproduces the experimental curves of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
3
1
Order By: Relevance
“…Our results are consistent with their observations. However, the results presented here are in contrast to the published facts (17,20,21) for the H0C1/HC102 reaction at pH <5.0, where it is reported that the reaction produces both chlorine dioxide and chlorate ion. In this context, from the earlier reports, it is not clear whether the two products are formed in parallel or consecutive reactions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are consistent with their observations. However, the results presented here are in contrast to the published facts (17,20,21) for the H0C1/HC102 reaction at pH <5.0, where it is reported that the reaction produces both chlorine dioxide and chlorate ion. In this context, from the earlier reports, it is not clear whether the two products are formed in parallel or consecutive reactions.…”
Section: Discussioncontrasting
confidence: 99%
“…However, no detailed mechanistic information appears to be available in the literature for reactions 1 and 4. Our observation that the contribution of reaction 1 increases with decreasing pH values in the reaction between free chlorine and C102' in the pH 6.4-10.0 range is consistent with previous reports (8,20,21,31) that C102 formation is dominant only at low pH values.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Bromine dioxide is a highly reactive compound that is capable of disproportionating to form BrO 2 - and BrO 3 - . However, this does not take place because the concentration of BrO 2 is very low compared to ClO 2 so that the reactions in eqs 3 and 4 generate ClO 3 - and regenerate BrO 2 - . The reaction between BrO 2 and ClO 2 has been proposed as an intermediate step in the reduction of bromate ion by chlorous acid. , The rate constant for the BrO 2 /ClO 2 reaction at 1.0−2.0 M [H + ] has been estimated to be 1.2 × 10 5 M -1 s -1 . Thermodynamically, eqs 3 and 4 are very favorable and overcome the unfavorable step in eq 2.…”
Section: Resultsmentioning
confidence: 99%
“…As a result the last couple of decades have witnessed intense studies of various oxyhalogen-based systems via monitoring the reactants, intermediates, and/or products by different spectroscopic techniques such as UV–vis and stopped-flow technique in order to establish reliable kinetic models and to obtain thorough insight into their mechanisms. The list, of course, does not end here; further examples of such systems as the bromate–chlorite, hypochlorous acid–chlorite, chlorate–bromide, chlorate–chloride, iodide–iodate, and periodate–bromide reactions may also be provided after a survey of the literature. Checking the reported mechanisms of these systems has revealed that crucial short-lived intermediates (halogen oxides with different compositions) are considered to be involved for explanation of the kinetic behaviors.…”
Section: Introductionmentioning
confidence: 99%